PEMANFAATAN APPLICATION PROGRAMMING INTERFACE BMKG SEBAGAI VALIDASI SENSOR ADXL335 UNTUK PERINGATAN DINI GEMPA - Glorio Stephen Tham Glorio (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Indonesia is located in the Ring of Fire zone, making a reliable and low-cost earthquake early warning system essential. This study designs an early warning prototype using an accelerometer sensor that is validated in real time through the Meteorology, Climatology, and Geophysical Agency (BMKG) earthquake Application Programming Interface (API). The objectives of this research are to utilize the BMKG API as a validation tool for the accelerometer sensor in earthquake early warning systems, to analyze the estimated upload time of ADXL335 sensor data and BMKG API data based on internet network speed, and to evaluate the effectiveness of implementing an early warning system that integrates the ADXL335 sensor and BMKG API in providing real-time earthquake alerts. The results show that the use of the Application Programming Interface as a validation method for the ADXL335 sensor in earthquake early warning systems is capable of validating local readings using official BMKG data (endpoint gempaterkini.json), thereby reducing false alarms caused by non-seismic vibrations and increasing warning credibility. Furthermore, the system is able to send notifications within ≤ 5 seconds. This demonstrates that the combination of the ADXL335 sensor and BMKG API is effective as a low-cost solution for expanding the earthquake early warning network in Indonesia.